A behavioral framework for measuring motility: Linking past mobility experiences, motility and eudemonic well-being. (November 2020) - Shliselberg, Rebecca; Givoni, Moshe; Kaplan, Sigal
Graphical abstract: Highlights: Past mobility experiences and acquired travel resources contribute to motility. Motility can be quantitatively assessed through disaggregate measures of access, skills and willingness. Motility can be quantitatively linked to eudemonic well-being. Abstract: This study establishes a quantitative relationship between formative mobility, motility and eudemonic well-being. The behavioral framework is proposed as an aid for measuring motility, understanding its driving forces and its derived eudemonic well-being. Formative mobility consists of past mobility experiences, aquired mobility resources and socio-economic characteristics. Motility is assessed through components of personal access, skills and cognitive appropriation and cover: neighborhood mobility qualities, residential access qualities, mobility skills, travel self-confidence, openness to new people and places. Eudemonic well-being is measured using the three aspects of the Self-Determination Theory: autonomy, relatedness and competencies. A tailor made questionnaire was designed to collect the data. The proposed behavioral framework is validated with a structural-equation model estimated based on a sample of 822 women in Israel. The results show: i) past mobility experiences and aquired travel resources are positively correlated with current perceived motility, ii) mobility skills, travel self-confidence, openness to new people and places are associated with autonomy and environmental mastery, ii) openness to people and places is linked to a higher degree of self-acceptance, iii) mobility skills are positively related to higher personal growth and purpose, iv) access, mobility skills and openness to new people and places is linked to positive relations with others (relatedness).